Tales of the peculiar - Riggs, Ransom 1979- (Syndrigast Publications, 2016)
"Fictional historian Millard Nullings edits a collection of folk tales and legends known to contain information about the world of the peculiars, as introduced in Ransom Riggs' Miss Peregrine's Peculiar Children series"...